Texas and Southwestern Cattle Raisers Association Members' Preferred Sources of Animal Health Information - Patrick R. Allen; Traci L. Naile; Tom A. Vestal; Monty Dozier (Journal of Applied Communications, 2014)
The nation’s agriculture and food infrastructure is vulnerable to significant social disruption and economic loss from hazards. Biological hazards, such as animal disease epidemics, have resulted in millions of dollars of economic loss and the death of millions of livestock in the past, and it will happen again unless infrastructure stakeholders adopt proper preventative measures. From farm to plate, defense starts on the farm with producers. With the multitude of potential hazards, many factors influence livestock producers’ protective action decision process. A major factor in the decision to take a protective action is from where or from whom the threat information originates. By identifying preferred sources, perceived credible sources, and preferred formats of animal health information by producers, risk communicators can more effectively develop critical animal health warnings and messages to promote rapid detection of hazards. This study targeted 7,661 members of the Texas and Southwestern Cattle Raisers Association. An online questionnaire developed from previous research with similar populations allowed TSCRA members to respond to questions related to the objectives of this study. A representative sample of TSCRA members from Texas, Oklahoma, and New Mexico responded and identified high levels of perceived trust and reliability in local veterinarians as a source of information along with livestock associations and county extension offices. TSCRA members also indicated they have multiple preferred formats for receiving animal health information. By using this information when communicating possible hazards, protective action from such threats will become more probable in this population.
Keywords: Agrosecurity; vulnerability; animal health; protective active decision model; information sources; disaster management; risk communication